2017
DOI: 10.15171/mejdd.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Seronegative Celiac Disease in Adults in Pakistan: A Pilot Study

Abstract: BACKGROUND Celiac disease (CD) is usually missed, if the serology is negative. We aimed to evaluate the clinicopathological characteristics of seronegative CD (SNCD) and its response to gluten-free diet (GFD) in adult patients. METHODS This observational study was carried out at the Department of Hepatogastroenterology, Sindh Institute of Urology and Transplantation, Karachi, Pakistan from 2009 to 2015. All consecutive adult patients (≥17 years) with features of marked villous atrophy (Marsh class≥III) on duod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…This finding is compatible with previous studies in which the reported positivity for HLA DQ2 was 85.71% and 75%. 27,28 We found that patients with SNCD had a milder degree of villous atrophy with five (38.46%) patients showed Marsh 2, three (23.07%) Marsh 3a, three (23.07%) Marsh 3b, and only two (15.38%) patients had Marsh 3c stage. These results are similar to published studies that showed seropositive patients have a proportionately greater degree of villous atrophy than seronegative patients in various studies.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This finding is compatible with previous studies in which the reported positivity for HLA DQ2 was 85.71% and 75%. 27,28 We found that patients with SNCD had a milder degree of villous atrophy with five (38.46%) patients showed Marsh 2, three (23.07%) Marsh 3a, three (23.07%) Marsh 3b, and only two (15.38%) patients had Marsh 3c stage. These results are similar to published studies that showed seropositive patients have a proportionately greater degree of villous atrophy than seronegative patients in various studies.…”
Section: Discussionmentioning
confidence: 79%
“…27 At the end of 6 months, 10 patients were available for follow-up, and all responded to GFD, which is similar to earlier studies. 28,30 The classical clinical features, including diarrhea, abdominal pain, anemia, and weight loss, were more common in patients with SNCD compared with seropositive patients. These results are in concordance with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies [24, 26, 28, 40, 44] reported on the presence of diarrhea at diagnosis, all were included in the analysis of double vs. single dose of HLA-DQB1*02 and that of double vs. zero dose of the allele, as well. We failed to detect a significant gene dose effect, nor in the subgroups of children and adults in a homogeneous dataset (I 2 = 0.0%) (Table 2, S1 and S2 Figs).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the severity of villous atrophy, seven [12, 24, 25, 4144] and eight studies [12, 24, 25, 4145] were eligible for inclusion in the analysis of double vs. single dose of HLA-DQB1*02 and that of double vs. zero dose of the allele. Marsh 3c at diagnosis was not more frequent in patients with a double dose of HLA-DQB1*02, as compared to single and zero doses of the allele (OR = 0.870, CI: 0.514 to 1.470, p = 0.602 [I 2 = 39.7%, p = 0.127] and OR = 0.822, CI: 0.333 to 2.032, p = 0.671 [I 2 = 46.8%, p = 0.068], respectively).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the different study designs and diagnostic criteria adopted, endpoints and limited sample sizes of the populations under investigation in previous studies. 4,10,11,[13][14][15][16][17][18][19][20][21][22][23][24] Sensitivity and specificity of serological markers for coeliac disease have improved over the last few years, 25 thus making it more difficult to define the real prevalence of this condition. Indeed, debate exists on whether to consider positive coeliac IgG based serology in the context of IgA deficiency as seronegative coeliac disease, 9,10 or instead as a conventional form of coeliac disease associated with IgA deficiency.…”
Section: Introductionmentioning
confidence: 99%